Stacked polymer waveguide type fan‐in/fan‐out device for dense multi‐core fibre. Issue 4 (1st August 2015) - Watanabe, Tatsuhiko; Kokubun, Yasuo
Abstract : A compact fan‐in/fan‐out waveguide device for 19‐core uncoupled multi‐core fibre (MCF) was demonstrated using laminated polymer waveguide. The core was made of poly‐methyl‐methacrylate and the cladding was made of ultra‐violet (UV) cured epoxy resin which is solvent‐free oligomer. Since the oligomer does not shrink after UV‐curing, the surface of the cladding over the core ridge was flattened and the multiple layers can be laminated. The accurate core alignment in the vertical direction was realised by controlling the spin‐coat condition of cladding material precisely. The insertion loss from a 19‐core fibre to 19 single‐core fibres was measured to be <20 dB and the sum of the cross‐talk from all neighbouring cores was lower than −40 dB. The coupling loss which is caused by the offset of the core position and the spot size mismatch at the facet between the MCF core and the waveguide was <1.8 dB. It was shown that the coupling loss and the insertion loss can be improved by adopting a properly selected pair of polymer materials with appropriate value of index contrast and low absorption loss.